Pengaruh Kualitas Pelayanan Terhadap Kepuasan Anggota KJKS KUM3 Rahmat Surabaya - Dharmawati, Erni; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2018)
The aim of this research to determins the effect of service quality on satis facation of KJKS KUM3 Rahmat Surabaya members. To measure service quality sharia the advantage Compliances with Islamic Low which was known as CARTER (Compliance, Assurance, Reliability, Tangible, Emphaty, dan Responsiveness). This type of research is a casual associative by quantitative approach. The population in the research one members of KJKS KUM3 Rahmat Surabaya. the samplein this study is 89 members of KJKS KUM3 Rahmat Surabaya, who selected using non probability sampling method by using purposive sampling technique. The date were analyzed by hypothers testing. Result of this research shows that there is significany influence of service quality variabel on satisfaction of KJKS KUM3 Rahmat Surabaya members. The service quality variabel has a value 0f 8.710 and supported with sig value of 0,00 which if the sig value is smaller than 0,05 can be said have a significant influence.